2021
DOI: 10.2214/ajr.20.23935
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Outcomes of Architectural Distortion on Tomosynthesis: A Systematic Review and Meta-Analysis

Abstract: The publication of this Accepted Manuscript is provided to give early visibility to the contents of the article, which will undergo additional copyediting, typesetting, and review before it is published in its final form. During the production process, errors may be discovered that could affect the content of the Accepted Manuscript. All legal disclaimers that apply to the journal pertain. The reader is cautioned to consult the definitive version of record before relying on the contents of this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
4
15
0
Order By: Relevance
“…In our study, architectural distortion without a US/MRI correlate was less likely to represent malignancy than AD with a correlate (p < 0.05); sonographic [15][16][17][18][19][20][21] and MRI [22] correlation also emerged in the literature. All ADs require an ultrasound check; in fact AD at DBT is less likely to represent malignancy without correlative findings on US [21]; nonetheless, it is still a prerequisite to undergoing biopsy, given that the risk of malignancy is nearly 30% [21,23].…”
Section: Discussionsupporting
confidence: 61%
“…In our study, architectural distortion without a US/MRI correlate was less likely to represent malignancy than AD with a correlate (p < 0.05); sonographic [15][16][17][18][19][20][21] and MRI [22] correlation also emerged in the literature. All ADs require an ultrasound check; in fact AD at DBT is less likely to represent malignancy without correlative findings on US [21]; nonetheless, it is still a prerequisite to undergoing biopsy, given that the risk of malignancy is nearly 30% [21,23].…”
Section: Discussionsupporting
confidence: 61%
“…In addition, AD without correlative findings on ultrasound are less likely to represent malignancy [7,8,13]. Several studies [7][8][9][10][11]14] have reported that AD detected exclusively at DBT (with or without ultrasound correlate) are associated with significant risk of malignancy -ranging Abbreviations: AD, Architectural distortion; DBT, Digital breast tomosynthesis; 2D, mammography; DBT-VAB, Digital breast tomosynthesis-vacuum assisted biopsy. from 10.2% [10] to 50.7% [7].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that imaging surveillance rather than surgery can be considered for architectural distortion on DBT yielding radial scar and other benign pathologies without atypia at biopsy. Given the high malignancy rate of architectural distortion on DBT, core needle biopsy continues to be recommended even when a sonographic correlate is absent [10][11][12]. However,…”
Section: Discussionmentioning
confidence: 99%
“…While DBT-detected architectural distortion is less likely to be a manifestation of cancer than is DM-detected distortion, the associated malignancy risk is sufficiently high that routine biopsy is required for histological analysis [10][11][12]. Surgical excision has long been advocated for the management of DM-detected architectural distortion; however, more recent evidence suggests that surgical excision of DM-…”
Section: Introductionmentioning
confidence: 99%